Disease prevalence, disease incidence, and mortality in the United States and in England - James Banks; Alastair Muriel; James P. Smith (Institute for the Study of Labor (IZA), 2010)
We find disease incidence and prevalence are both higher among Americans in age groups 55-64 and 70-80 indicating that Americans suffer from higher past cumulative disease risk and experience higher immediate risk of new disease onset compared to the English. In contrast, age specific mortality rates are similar in the two countries with an even higher risk among the English after age 65. Our second aim explains large financial gradients in mortality in the two countries. Among 55-64 year olds, we estimate similar health gradients in income and wealth in both countries, but for 70-80 year old, we find no income gradient in UK. Standard behavioral risk factors (work, marriage, obesity, exercise, and smoking) almost fully explain income gradients among 55-64 years old in both countries and a significant part among Americans 70-80 years old. The most likely explanation of no English income gradient relates to their income benefit system. Below the median, retirement benefits are largely flat and independent of past income and hence past health during the working years. Finally, we report evidence using a long panel of American respondents that their subsequent mortality is not related to large changes in wealth experienced during the prior ten year period.
Keywords: I10; 330; Health; Gesundheit; Sterblichkeit; Einkommen; Vermögen; Vergleich; USA; Großbritannien